If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3(y+1)+7y=-4(y+1)-7
We move all terms to the left:
-3(y+1)+7y-(-4(y+1)-7)=0
We add all the numbers together, and all the variables
7y-3(y+1)-(-4(y+1)-7)=0
We multiply parentheses
7y-3y-(-4(y+1)-7)-3=0
We calculate terms in parentheses: -(-4(y+1)-7), so:We add all the numbers together, and all the variables
-4(y+1)-7
We multiply parentheses
-4y-4-7
We add all the numbers together, and all the variables
-4y-11
Back to the equation:
-(-4y-11)
4y-(-4y-11)-3=0
We get rid of parentheses
4y+4y+11-3=0
We add all the numbers together, and all the variables
8y+8=0
We move all terms containing y to the left, all other terms to the right
8y=-8
y=-8/8
y=-1
| 5x-3=+14x | | -7s−6=-6s | | 4(w-9)=2w-20 | | 10t+9=9t | | X+5.5+8=5x | | 40+9b=112 | | -10q−10=-5q | | 12=a/2 | | 5-3h=5h | | 8g=-10+9g | | g2+4g+2=0 | | 11x=3-5 | | 4g+3=2g+9 | | (x-1)/2=x+7 | | 5y-1÷2=2y+3 | | 5x+6/5=-3x+7/7 | | -4+3w=4w | | -7=2(r-8)-9 | | 5x-1÷2=2x=3 | | X^2-x-24=6 | | 18m+15=78 | | 16/5a-5/16a=462 | | 13-5y-y=7 | | 46-2x=8x-16 | | 11a^2-5a+11=0 | | w+-3=-4 | | 7.2+5.2f=8.76 | | -3(2t+1)=21 | | x-22+1=4x-53 | | x-0,7x=2550000 | | 10x2-8x-6=0 | | 12.5z–6.4=–8z+3(1.5z–0.5) |